Situation report on Nepal’s agrifood systems : July 2023 - Kumar, A.; Palikhe, A.; Maharjan, N.K.; Adhikar, M.; Gupta, S.; Minot, Nicholas; Dorosh, Paul A.; Kishore, Avinash; Koirala, Pankaj; Krupnik, Timothy J. (CSISA, 2023)
In June 2023, Nepal witnessed a slight increase in the prices of food and beverages by 1.3 percent as compared to the previous month. The inflation rate of non-food items and services conversely decreased marginally. This can be partially attributed to a decline in transportation costs. There was a deceleration in the year-on-year Consumer Price Index (CPI), reaching 6.8 percent this month compared to a 10.1 percent increase in the Wage Rate Index.